Aspectos da favelização em Ribeirão Preto – SP: revelando vivências - Rosa, Lucelina Rosseti (2008)
This research approaches the urban issues causing a consideration about the way of life in cities in the present time, through a survey in Ribeirão Preto, countryside in São Paulo state. We focused the paper on investigating part of the process of slummy effect that expands in the outskirts of this city, having the object of analysis the “Favela da Coca-Cola Slum”. Putting our efforts to understand the reason why such social configuration expands, we screened one of the dwellers, its history and background. By having the guiding assumption relation/interaction between rural and urban, country and city, we found in the concepts of 'agrobusiness' and the 'country side metropolis' components to understand the historical social differences built by the developing of Ribeirão Preto. Thus, the slummy effect seems to be the tool to expose the devices found through social roles that seek to 'survive' in the urban spaces by developing their own ways to live in the city space.